The Analysis of Audit Quality on Investor Trust in the Capital Market: A Case Study of Company X in Jakarta - Nikma Bilondatu (Economics and Digital Business Review, 2025)
This study investigates the effect of audit quality on investor trust in the Indonesian capital market, using Company X in Jakarta as a case study. Investor trust is considered a crucial factor for capital market efficiency, and audit quality serves as an important mechanism to reduce information asymmetry between managers and shareholders. Drawing upon agency theory, signaling theory, and stakeholder theory, the research examines how audit quality influences investor trust, with auditor reputation and Key Audit Matter (KAM) disclosures as moderating factors. A quantitative case study approach was applied. Primary data were collected through surveys of institutional and retail investors, while secondary data were obtained from Company X’s audited financial statements and Indonesia Stock Exchange (IDX) reports. The study employed Structural Equation Modeling (SEM) to test the hypothesized relationships. The results reveal that audit quality has a significant positive effect on investor trust. Auditor reputation, particularly the engagement of a Big 4 auditor, strengthens this relationship, while KAM disclosures have a positive but weaker moderating effect. These findings highlight the importance of credible audits and transparent disclosures in building investor confidence, especially in emerging markets. This research contributes to the literature on audit quality and investor behavior by providing evidence from Indonesia, and offers practical implications for companies, auditors, and regulators seeking to enhance trust and transparency in capital markets.